Exosome-derived FGD5-AS1 promotes tumor-associated macrophage M2 polarization-mediated pancreatic cancer cell proliferation and metastasis. (1st November 2022) - He, Zhiwei; Wang, Jie; Zhu, Changhao; Xu, Jian; Chen, Peng; Jiang, Xueyi; Chen, Yankun; Jiang, Jianxin; Sun, Chengyi
Abstract: Inflammatory molecules and exosomes are crucial for signal transduction between tumor-associated macrophages and tumor cells. IL-6, a key inflammatory molecule secreted by M2 macrophages after polarization, can mediate malignant progression of pancreatic cancer (PC). However, the functions and mechanisms of IL-6 and tumor-derived exosomes in tumor-associated macrophages and PC remain unclear. Transcriptome chip and quantitative reverse transcription PCR experiments indicated that FGD5-AS1 induced IL-6 and high FGD5-AS1 expression correlated with the poor prognosis in PC patients. RNA pulldown, mass spectrometry, and dual luciferase reporter assays were used to identify the mechanism of exosomal FGD5-AS1 in promoting PC progression and M2 macrophage polarization. FGD5-AS1 exerted cancer-promoting functions when co-cultured with M2 macrophages. PC-derived exosomal FGD5-AS1 stimulated M2 macrophage polarization by activating STAT3/NF-κB pathway. FGD5-AS1 interacts with p300, resulting in STAT3 acetylation, thus promoting nuclear localization and transcriptional activity of STAT3/NF-κB. These data indicated that PC cells generate FGD5-AS1-rich exosomes, which cause M2 macrophage polarization to promote the malignant behaviors of PC cells. Targeting exosomal FGD5-AS1 may provide a potential diagnosis and treatment strategy for PC. Highlights: Exosomal FGD5-AS1 exhibits tumor promoting activities on tumor cells and macrophages. FGD5-AS1 activated STAT3/NF-κB signaling pathway. Macrophage M2 polarization by FGD5-AS1 promote malignant behaviors of PC cells. Targeting exosomal FGD5-AS1 may help in developing novel treatment strategy for PC.